Spontaneous delivery is associated with increased endothelial activity in cord blood compared to elective cesarean section. (August 2020) - Sibikova, Michaela; Vitkova, Veronika; Jamrichova, Linda; Haluzik, Martin; Zivny, Jan; Janota, Jan
Abstract: Objectives: It is suggested that delivery whether spontaneous or by elective cesarean section is associated with an inflammatory reaction which may be modified by the type of delivery. Inflammatory reactions are associated with endothelial activation. The aim of our study was to assess endothelial biomarkers in cord and neonatal blood following different modes of delivery. Study design: The study group consisted of term healthy newborns after uncomplicated pregnancies and either spontaneous vaginal delivery (n = 39) or elective cesarean section (n = 20). Plasma soluble biomarkers were measured using multiplex magnetic bead immunoassay. The microvesicle count and number of surface antigen-specific microvesicles were determined by flow cytometry. Results: We found significantly increased concentrations of cord blood endothelial markers (sVEGFR1, Endothelin-1 and sVCAM1) and microvesicles (EPCR/CD201+, ICAM1/CD54+ and PECAM1/CD31+) in spontaneous vaginal delivery when compared to elective cesarean section. Irrespective of the delivery mode endothelial markers sVEGFR1, Endocan, Angiopoietin-2, VEGF, and sICAM1, were significantly increased in neonatal compared to cord blood. Conclusion: We found increased cord blood concentrations of endothelial markers and microvesicles following spontaneous vaginal delivery, which may reflect the natural activation of endothelial cells during labor. Following the delivery, most of the soluble markers increased, as a possible consequence of activation of neonatal innate immunity and postnatal cardiovascular transition.